2012
DOI: 10.1029/2012jc007927
|View full text |Cite
|
Sign up to set email alerts
|

Eddy contributions to the meridional transport of salt in the North Atlantic

Abstract: [1] The meridional transport of salt in the Atlantic ocean is an important process for climate, controlling the stability of the meridional overturning circulation. The contribution of transient eddies to this transport is quantified in an eddy resolving North Atlantic model at 1/12 resolution (NATL12), and compared with lower resolution North-Atlantic and global 1/4 models. In NATL12 between 10 N and 40 N, there is a volume loss by evaporation of 0.6 Sverdrups (Sv). The divergence of the eddy flux of salt (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
82
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 51 publications
14
82
1
Order By: Relevance
“…At 26.5°N the uncorrected value for M ov was -0.55 Sv, while after applying the velocity bias correction it becomes -0.67 Sv. One of the reasons for velocity biases might be that eddies play an important role in the total freshwater budget and they are underestimated in coarse resolution models (Tréguier et al, 2012;Mecking et al, 2016). The latter study also found that freshwater transport by the gyre can become much stronger in an eddy-permitting model, allowing for a stronger negative M ov .…”
Section: Conclusion and Discussionmentioning
confidence: 49%
“…At 26.5°N the uncorrected value for M ov was -0.55 Sv, while after applying the velocity bias correction it becomes -0.67 Sv. One of the reasons for velocity biases might be that eddies play an important role in the total freshwater budget and they are underestimated in coarse resolution models (Tréguier et al, 2012;Mecking et al, 2016). The latter study also found that freshwater transport by the gyre can become much stronger in an eddy-permitting model, allowing for a stronger negative M ov .…”
Section: Conclusion and Discussionmentioning
confidence: 49%
“…However, HEDDY and HADV may also vary in phase during some events (the 1999 freshening, Figure 9b). Gross negative correlation between eddy and mean horizontal salt transport is a very striking characteristic also present in other eddy resolving ocean simulations [Treguier et al, 2012]. Although the magnitude of interannual variations of the surface salt flux (SSF) is weaker than that of the other term, its contribution cannot be quantified as negligible (Figure 9b).…”
Section: Modelmentioning
confidence: 84%
“…It is worth noting that this feature, present in many coarse and eddy-permitting models (e.g. Danabasoglu et al, 2014;Grist et al, 2010), is absent in GLOB16, likely due to a correct path of the simulated North Atlantic Current (Dan- abasoglu et al, 2014; Treguier et al, 2012), as described in Sect. 3.6.…”
Section: Volume and Heat Transportsmentioning
confidence: 99%